Układ sił politycznych w Dumie Państwowej Rosji trzeciej kadencji - Stelmach, Andrzej (Wyższa Szkoła Zarządzanie i Bankowości, 2000)
The prevailing political power structure in Russian Duma reflects the actual political atomisation of Russian society, The mixed right to vote contributes to the internal political breaking up of the Parliament. Further, the election of a half of deputies by one-mandate constituencies is the chance to win the mandate not only by small, local political parties but also by individuals who lack any political support. However, 50% of the mandates is reserved for the biggest political groups, i,e. these which managed to exceed the threshold of 5%. The result is that the Lower House of Parliament has failed, so far, to establish any coalition of majority. Such a situation is favoured by the specific presidential lbrm of authority in Russia.
Political power structure in the third cadence of Russian Duma
Keywords: siły polityczne; Rosja; political forces; Russia